The Influence of Problem-Based Learning Models on Students' Critical Thinking Skills Reviewed from Cognitive Style - Hidayatullah, Nisa; Gunada, I Wayan; Susilawati, Susilawati; Zuhdi, Muhammad (Journal of Science and Science Education, 2025)
This study aims to analyze the effect of problem-based learning models on students' critical thinking skills in terms of cognitive style, analyze the effect of cognitive style on students' critical thinking skills, and analyze the interaction between problem-based learning models and cognitive styles on students' critical thinking skills. The type of research used is quasi-experimental with a factorial design research design. The population in this study were all students of class XI IPA at MAN 1 Central Lombok. The research sample was taken using a purposive sampling technique. The data collection technique in this study was taken using an instrument for students' critical thinking skills: a descriptive test of 10 questions and data collection of cognitive styles using the Group Embedded Figure Test (GEFT) instrument. The research hypothesis was tested using a two-way ANOVA test. The study results showed that: 1) there is an influence on students' critical thinking skills based on the problem-based learning model with a significant level of 0.000 <0.050. 2) cognitive style influences students' critical thinking skills with a significant level value of 0.001 <0.050. 3) there is no interaction between cognitive style and problem-based learning model on students' critical thinking ability with a significance level of 0.097>0.050. Thus, it means that the problem-based learning model influences students' critical thinking ability, cognitive style influences students' critical thinking ability, and there is no interaction between cognitive style and learning model on students' critical thinking ability